How do pregnant women's perceptions of obstetric forceps change according to their demographic background: a cross sectional study - Jasmine M. Hitt; Angela S. Martin; Jordan E. Dietrich; Natasha Ahmed; Gene T. Lee (BMC, 2021)
Abstract Background Women's attitudes towards obstetric forceps likely contribute to declining use and opportunities for residency training, but formal documentation of women's attitudes towards obstetric forceps is currently limited. A clearer understanding should help guide our attempts to preserve its use in modern obstetrics and to improve residency training. Our objective is to document women's attitudes towards obstetric forceps and the influence basic demographic variables have on those attitudes. Methods A cross sectional study was performed. We developed a one-time anonymous structured 5-question survey that was given to all women with low-risk pregnancies presenting to our medical center for prenatal care between October 2018-December 2018. The questionnaire asked for the woman's self-reported age, race, education level and insurance type. The five questions were as follows: (1) Do you think forceps should be used to deliver babies, (2) Is forceps safe for the baby, (3) Is forceps safe for the mother, (4) Do you think forceps can help to lower the cesarean section rate, (5) Do you think physicians in training should learn to place forceps on a real patient. We calculated means and proportions for the responses according to the overall group and various subgroups. Statistical analysis included Kruskall-Wallis or Mann-Whitney tests as appropriate. Results were also adjusted by regression using a Generalized Linear Model. Power calculation showed sample size of 384 was required. Results A total of 499 women returned the questionnaire. Response rate was 56.8% (499/878). The findings suggest that women's perceptions towards forceps are generally negative. Women with white ethnicity, college education or higher and private insurance did have more favorable views than their counterparts, but the majority still had unfavorable views. Age was not shown to have a significant effect on maternal attitude. Conclusion Women's views towards forceps use in the University of Kansas Medical Center are negative and may be contributing to the decline of its use. Improving women's perceptions of forceps would require multiple different strategies rather than a single focused easily-implemented message. If forceps training continues, such training will rely on a minority of women who will accept forceps use in childbirth.